Keterwakilan 30% Perempuan di Parlemen: Sebuah Refleksi Menyambut Pemilu 2024 - Rizky Octa Putri Charin (Social Issues Quarterly, 2023)
Women's participation in politics is expected to be able to contribute significantly and be able to change views on "politics" itself, as well as the relationship between the state and the people dramatically. This change is expected to improve the political image which has been considered as a “hard and dirty” work area, where this arena is mostly filled by men. Since Indonesia was established as a country, the number of women's participation and representation in the political arena is still very low and marginalized. This is certainly not in line with the spirit of the country's constitution which guarantees equal rights for women and men to participate in formal politics. This means that women certainly also have the right to vote and be elected to public and political positions. The existence of an open electoral system has provided an opportunity for women to participate in political representation. However, efforts to achieve gender justice in elections are still faced many obstacles, especially affirmative action on the women's quota system. Although the quota system is guaranteed by law, the patriarchal system remains the main obstacle in efforts to increase the number of women's representation in Parliament.